Iranian Auditor’s Perceptions of Inherent Risk - Yahya Hassas Yeganeh; E. Vahidi Elizeei (مطالعات تجربی حسابداری مالی, 2004)
In year 1377, the Auditing organization in Iran issued its Statement of Auditing Standards 40 (SAS 40): "Accounting and Internal Control System and Audit Risk Assessment". The standard identifies inherent risk as one of the three components of   audit risk; inherent risk being defined as "the susceptibility of an account   balance or class of transactions to material misstatement". If the inherent risk is low, less substantive testing is required, with possible resultant savings in staff time and audit costs.  It is thus beneficial for the audit firms and clients to assess adequately   the inherent risk element of an audit assignment to ensure that audits are carried out as efficiently and effectively as possible. This   research    project   focuses   on   inherent    risk   and   using   a questionnaire    survey   investigates    143 auditors’    perception   of the importance of certain factors which may determine inherent risk. The finding  of the study suggests  that variables  identified  in the literature as being closely  associated  with inherent  risk factors  are regarded in a similar  fashion  by auditors;  variable  such as bonus  schemes tied to management  earnings,   a high   turnover rate in top   management personnel, a company reputation for taking unusual  business   risks and history of material errors are believed to be the  major determinants   of inherent  risk. Finally,  the evidence  revealed  that  (1) misunderstanding    the  significance   of  the  risk  factor  is  due  to  the disregard  of various  meaning  of the words.(2)  Auditors  had difficulty in distinguishing   between  inherent risk and control  risk factors.